2017
DOI: 10.1021/acs.analchem.7b03227
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gold Nanoparticle Ultraviolet–Visible Extinction, Absorption, and Scattering Cross-Section Spectra and Scattering Depolarization Spectra: The Effects of Nanoparticle Geometry, Solvent Composition, Ligand Functionalization, and Nanoparticle Aggregation

Abstract: Using the recent polarized resonance synchronous spectroscopic (PRS2) technique, we reported the quantification of photon extinction, absorption, scattering cross-section spectra, and scattering depolarization spectra for AuNPs of different sizes and shapes. The effects of the solvent composition, ligand functionalization, and nanoparticle aggregation on the AuNP photon absorption and scattering have also been experimentally quantified. The light scattering depolarization is close to 0 for gold nanospheres (Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…This enables us to reveal insights that have not been accessible before. We have recently demonstrated that light scattering depolarization is very sensitive to the deformation of the spherical AuNPs (Xu et al, 2018a). The silver-staining has no significant effect on the AuNPs light scattering depolarization spectrum, indicating that the AuNPs remain spherical after the silver-staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables us to reveal insights that have not been accessible before. We have recently demonstrated that light scattering depolarization is very sensitive to the deformation of the spherical AuNPs (Xu et al, 2018a). The silver-staining has no significant effect on the AuNPs light scattering depolarization spectrum, indicating that the AuNPs remain spherical after the silver-staining.…”
Section: Resultsmentioning
confidence: 99%
“…PRS2 is a new spectroscopic method that enables quantitative decomposition of the sample UV-vis extinction spectrum into its absorption extinction and scattering extinction spectrum. The theoretical background, spectral acquisition, and data analysis procedure are available in recent publications (Athukorale et al, 2017b; Siriwardana et al, 2017; Xu et al, 2018a,b). Briefly, the excitation polarization of the spectrofluorometer is set vertical (V) and the detection polarization is kept either vertical or horizontal (H) to acquire PRS2 VV or VH spectra, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the aggregation of the silver nanoparticle suspension was observed with 20‐mM NaCl and was characterized by an increase of both the average nanoparticle hydrodynamic size from 75 to 89 nm and the polydispersity index from 0.20 to about 0.40. An increase in UV–Vis absorption intensity at longer wavelength region (between 600 and 800 nm) was also observed due to the LSPR feature of the aggregated nanoparticles (Figure b) . In case of AuNPs, no significant evolution in UV–Vis (Figure c) or size distribution properties was observable when R6G solution was added indicating that the suspension remained in its initial long‐term stability state …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that in the absence of NaCl, the colloid aggregation was induced by the analyte as observed from absorbance sprectra (results not shown): an absorbance band appeared between 700 and 800 nm when adding R6G in FAuNPs 1 suspension due to the localized surface plasmonic resonance (LSPR) feature of aggregated gold nanoparticles while adsorption peak at 520 nm decreased due to the reduction in the number of monomeric gold nanoparticles [49]. Then NaCl addition made the absorbance band between 700 and 800 nm increasingly prominent due to an increasing degree of nanoparticles aggregation [49]. These more aggregated colloids led to significant enhancement of the Raman signal.…”
Section: Faunps Suspensions Several Batches Of Faunpsmentioning
confidence: 90%